2014
DOI: 10.1038/mi.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

Airway structural cells regulate TLR5-mediated mucosal adjuvant activity

Abstract: Antigen-presenting cell (APC) activation is enhanced by vaccine adjuvants. Most vaccines are based on the assumption that adjuvant activity of Toll-like receptor (TLR) agonists depends on direct, functional activation of APCs. Here, we sought to establish whether TLR stimulation in non-hematopoietic cells contributes to flagellin's mucosal adjuvant activity. Nasal administration of flagellin enhanced T-cell-mediated immunity, and systemic and secretory antibody responses to coadministered antigens in a TLR5-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 60 publications
15
72
0
Order By: Relevance
“…6E). As reported (39,40), an S. Typhimurium flagellin mutant lacking only the two carboxy-terminal amino acids (fliC ) also failed to activate Naip5-and Nlrc4-dependent inflammasome responses (Fig. 6 C-E).…”
Section: Asc Specks Are Dispensable For S Typhimurium-and Cytosolicmentioning
confidence: 77%
See 1 more Smart Citation
“…6E). As reported (39,40), an S. Typhimurium flagellin mutant lacking only the two carboxy-terminal amino acids (fliC ) also failed to activate Naip5-and Nlrc4-dependent inflammasome responses (Fig. 6 C-E).…”
Section: Asc Specks Are Dispensable For S Typhimurium-and Cytosolicmentioning
confidence: 77%
“…Gentamycin (50 μg/mL, 10131-027, Life Technologies) was added, and cell lysates were prepared 30 min later. In other experiments, recombinant H. pylori flagellin (flaA, HPA-5040, Austral Biologicals), or purified S. Typhimurium flagellin (fliC, 5 μg/mL) produced in E. coli (40) or 293T cells (fliC 293T ) was delivered in the cytosol using streptolysin O (SLO, 25 μg/mL, S5265-25KU, Sigma), as described (17). In some experiments, cells were pretreated with Ac-YVAD-cmk (50 μM, ALX-260-028-M001, Enzo Life Sciences) for 30 min before S. Typhimurium infection or fliC transfection.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the neutrophils in the therapeutic effect of the combination treatments and the influence of antimicrobial molecules remain to be elucidated. Furthermore, there is strong evidence to suggest that the primary targets of intranasally administered flagellin are the airway epithelial cells (20,21,38). The epithelial cells express TLR5 strongly and respond both in vitro and in vivo to flagellin by upregulating the transcription of genes encoding host antibacterials and phagocyte-specific chemokines (21,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…S1C to E in the supplemental material). Indeed, flagellin enhanced the transcription of Ccl20 and Cxcl1 (both surrogate markers of TLR5-mediated lung stimulation [21]) in animals from 0 to 24 h postinfection. These results indicated that flagellin is able to boost innate signaling even in the context of ongoing pneumococcal infection.…”
Section: Combined Administration Of Flagellin and Amx Improves The Trmentioning
confidence: 99%
See 1 more Smart Citation